Self-medication for Cough: a Study of Smokers and Non-smokers in Surabaya Colleges - Lorensia, Amelia; Suryadinata, Rivan Virlando; Hayati, Siti Nur; Suud, Suud (Global Medical & Health Communication (GMHC), 2024)
The number of smokers among students is increasing. Smoking can cause coughing, the body's defense mechanism for clearing the airways. Cough can be treated with self-medication, which can cause drug-related problems. The level of knowledge and perception can influence the choice of cough medicine used. The purpose of this study was to determine the knowledge and perceptions of cough medicine self-medication in smokers and non-smokers. This research method was a case-control study using a questionnaire of knowledge (definition, method of use, and indications) and perceptions (definition, side effects, and experience) regarding using self-medicated cough medicine. The research sample was adult students at a private university in Surabaya from January 2023 to April 2023, and it was collected using a purposive sampling method. The sample size was 124 respondents, 62 smoking and 62 non-smoking students. The level of knowledge in both groups was high, namely 51.62% in the smoker group and 58.84% in the non-smoker group. Meanwhile, the perception level in the smokers group was mostly bad (56.45%), in contrast to the non-smokers who had a good level of perception (64.52%). There was a significant difference in the level of knowledge (0.00) and perception (0.00) between smokers and non-smokers regarding cough medicine self-medication. Therefore, smokers have the same high level of expertise but lower levels of perception than non-smokers. Health promotion programs to increase knowledge are essential considerations in optimizing self-medication.